Identification of microbial diversity in buried ivory soil at the Sanxingdui site in Guanghan City, China, using high-throughput sequencing - Sun, Siyu; Xu, Zhe; Ren, Mengjia; Li, Sifan; Xie, Zhenbin; Luo, Yanbing; Tian, Yongqiang (Frontiers in Microbiology, 2024)
The Sanxingdui Site in Guanghan City, Sichuan Province, China, is one of the precious heritage sites of the ancient Chinese civilization. Archaeological work at Sanxingdui is of great significance in clarifying the origins and main contents of the ancient Shu culture and the Yangtze River civilization. Since the 1920s, archaeologists have conducted extensive excavations and research at the site, with particular attention given to the large number of ivory artifacts unearthed. However, the buried ivory is influenced by soil pH, temperature, humidity, and other physical and chemical factors, along with the potential impact of microbial activities that may lead to the corrosion and decomposition of ivory. By understanding the types and activities of microorganisms, appropriate measures can be taken to protect and preserve cultural relics.Methods: Multi-point sampling of soil samples around the ivory of the three sacrificial pits at the Sanxingdui site was carried out, and strict aseptic operation was carried out during the sampling process. Subsequently, the microbial community structure and diversity in the buried ivory soil of Sanxingdui site were identified and analyzed by Illumina high-throughput sequencing technology.Results: 16S rRNA and internal transcribed spacer sequence analysis revealed significant differences in the soil microbial community structure among different sacrificial pits. The dominant bacterial phyla were the Proteobacteria, GAL15, Actinobacteriota, Bacteroidota, and Methylomirabilota. The dominant fungal phyla were Ascomycota, Mortierellomhcota, and Basidiomycota. Most dominant bacterial and fungal communities play an indispensable role in the ivory corrosion mechanism, promoting the decay and decomposition process through various means such as decomposing organic matter and producing acidic substances. Discussion: It is particularly important to take a series of measures to control microbial activity to effectively protect ivory. Our preliminary study of the mechanism of action of microorganisms on ivory in a buried environment provides a scientific basis to prevent and protect against microbial degradation in ancient ivory unearthed in Sanxingdui. Following the research results, suitable antibacterial agents tailored to the preservation environment and microbial characteristics of ancient ivory can be prepared. Ensure that the selected antibacterial agents meet safety and effectiveness requirements to maximize protection against microbial degradation of ancient ivory.